PLANT DENSITY OF “ULTRA” AND “FLESH” WINTER WHEAT VARIETIES - Durdiyev, N.H.; G‘opporova, Z.I. (Research Focus International Scientific Journal, 2026)
This article examines the formation of plant density in winter wheat and the resistance of plants to winter cold based on field experiments conducted during 2024–2025. During the study, plant density before winter and in early spring, as well as the proportion of plants damaged by winter frost, were determined. According to the results, pre-winter plant density ranged from 451.4 to 471.4 thousand plants/m², while the early spring indicator varied between 401.4 and 455.8 thousand plants/m². The level of plant mortality caused by winter cold varied from 8.8% to 52.7% depending on the experimental variants and years.